PENGARUH CUSTOMER ORIENTATION DAN COMPETITOR ORIENTATION TERHADAP KINERJA BISNIS MELALUI INNOVATION CAPABILITY - Wijaya, Dicky; Subagio, Hartono (PERFORMA, 2025)
Micro, Small and Medium Enterprises (MSMEs) are the spearhead of the economy in Indonesia. This things is due to the contribution of MSMEs towards Indonesian economy quite large, that is, in the rate of 61 percent. Therefore, it is important for government or society to be able to develop MSMEs that exist in Indonesia to be better direction. The development of MSMEs can be in the form of Business Performance increase of MSMEs. As the effort to improve Business Performance, therefore each MSME has to have Innovation Capability. Innovation Capability itself is supported by two things, that is Customer Orientation and Competitor Orientation. The purpose of this research is to find out the effect of Customer Orientation on Innovation Capability and Business Performance, the effect of Competitor Orientation on Innovation Capability and Business Performance, the effect of Innovation Capability on Business Performance, and the ability of Innovation Capability mediates the effect of Customer Orientation and Competitor Orientation on Business Performance. This research is quantitative research by using Partial Least Square (PLS) method. As many as 60 respondents from SMEs in West Surabaya are used as research material. Data that is obtained is processed by using SmartPLS software. The result of this research shows that Customer Orientation affect significant on Innovation Capability and Business Performance, Competitor Orientation affect significant on Innovation Capability and Business Performance, Innovation Capability affect significant on Business Performance, and Innovation Capability is able to mediate the effect of Customer Orientation and Competitor Orientation on Business Performance.